Hotel selection using a modified TOPSIS-based decision support algorithm - Kwok, P.K.; Lau, Henry Y.K. (Decision Support Systems, 2019)
While many studies pointed out that travellers often consider a basket of factors when they are selecting their accommodation, few online travel agency websites allow the travellers to actively express their preference about the selection criteria in order to receive tailor-made recommendations in return. The absence of this feature causes travellers to spend extra effort and time to compare the hotel options themselves. This paper presents a decision support algorithm, namely Vague Set TOPSIS, to help travellers to rank the hotel options. It was found in this research that the structure and assumptions of the conventional TOPSIS methods are not suitable for handling this decision problem. Therefore, this paper is novel in providing a foundational change to the conventional TOPSIS models such that it is more applicable to hotel selection. The validity of the proposed decision support algorithm was proved via three approaches, which are mathematical proofs, computer stochastic simulation experiments and a numerical case study using data obtained from Hotels.com. [Display omitted]